PENERAPAN METODE PQRST (PREVIEW QUESTION READ STATE TEST) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V D SD NEGERI 004 TEMBILAHAN - Fernandes Ali (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low results of fifth grade students learn math SD Negeri 004 Tembilahan. It is seen from the acquisition value of the average results of students' mathematics learning of 68. The cause of poor performance of student learning are: a) the students are passive in learning; (b) less active students in learning; (c) the lack of a medium of learning so that students can interact directly with the subject matter; and (d) the ability of students to understand math concepts low. Based on this, the researchers apply the PQRST method to improve mathematics learning outcomes through action research. This study was conducted in 004 SD Negeri Tembilahan, the subject of this study is the fifth grade students with 28 students. This study was conducted in two cycles, in which the flow of research is the planning stage, deploy stage, the stage of observation and reflection stages. The results stated That mathematical results have increased after learning the PQRST method (Preview Question Read State Test). It can be seen from the increase in mathematics learning outcomes on the basis of 64.67% category scores enough, the first cycle of 64.67% remains well enough categories, and the second cycle, 86.67% excellent category, with the percentage increase 22.00%.